Fraud Detection Credit Card: A Bibliometric Analysis Approach - Risky Mezi Muria (Lafadz Jaya Publisher, 2023)
The aim of this research is to provide research possibilities for future research. This research uses bibliometrics. Samples of journals or articles after going through a selection process with purposive sampling of 50 journals or articles from 2017-2021. Data sources come from journals and articles published in Science Direct, Emerald Insight and Google Scholar. The results of this research are that Google Scholar is the source of the most popular journals or articles and IEEE is the largest publication in credit card fraud detection publications. Opportunities for further research could be to apply some of the proposed new methods to various types of credit card fraud data.